Impact of Vacuum-Assisted Venous Drainage on Forward Flow in Simulated Pediatric Cardiopulmonary Bypass Circuits Utilizing a Centrifugal Arterial Pump Head - Guimarães,Daniel Peres (2020)
Abstract Objective: To analyze the impact of vacuum-assisted venous drainage (VAVD) on arterial pump flow in a simulated pediatric cardiopulmonary bypass circuit utilizing a centrifugal pump (CP) with an external arterial filter. Methods: The simulation circuit consisted of a Quadrox-I Pediatric oxygenator, a Rotaflow CP (Maquet Cardiopulmonary AG, Rastatt, Germany), and a custom pediatric tubing set primed with Lactated Ringer's solution and packed red blood cells. Venous line pressure, reservoir pressure, and arterial flow were measured with VAVD turned off to record baseline values. Four other conditions were tested with progressively higher vacuum pressures (-20, -40, -60, and -80 mmHg) applied to the baseline cardiotomy pressure. An arterial filter was placed into the circuit and arterial flow was measured with the purge line in both open and closed positions. These trials were repeated at set arterial flow rates of 1500, 2000, and 2500 mL/min. Results: The use of progressively higher vacuum caused a reduction in effective arterial flow from 1490±0.00 to 590±0.00, from 2020±0.01 to 1220±0.00, and from 2490±0.0 to 1830±0.01 mL/min. Effective forward flow decreased with increased levels of VAVD. Conclusion: The use of VAVD reduces arterial flow when a CP is used as the main arterial pump. The reduction in the forward arterial flow increases as the vacuum level increases. The loss of forward flow is further reduced when the arterial filter purge line is kept in the recommended open position. An independent flow probe is essential to monitor pump flow during cardiopulmonary bypass.